Transplantation of engineered vascularized lymphatic tissue using LEC and in vivo AV loop model to enhance lymphangiogenesis and restore lymphatic drainage in a lymphadenectomy rat model - Mackert, Gina A.; Hsiao, Hui-Yi; Chang, Yung-Chun; Wu, Robin T.; Dang, Rushil R.; Tee, Richard; Huang, Jung-Ju (Journal of tissue engineering, 2025)
Lymphedema has emerged as a significant health issue among cancer survivors. The primary goal of treatment is to restore lymphatic drainage function. Engineering vascularized lymphatic tissue offers a promising alternative to achieve this goal. Currently, lymphatic tissue engineering with the use of cell-seeded scaffolds incubated in high hemodynamic flow environments, such as AV loop chambers, has shown promising results for lymphatic vessel regeneration. In this study, lymphatic endothelial cells (LECs) and adipose-derived stem cells (ASCs) were incorporated into an AV loop chamber and cultured in the groin region of a rat model. Surprisingly, the level of lymphangiogenesis, indicated by increased expression of the lymphatic marker LYVE-1, was significantly higher in the group with LECs alone than in the group with both LECs and ASCs. The engineered lymphatic tissue was subsequently orthotopically transplanted into the area of lymph node dissection. This procedure restored lymphatic drainage and reduced local inflammation, with decreased levels of CD3, CD4, and CD8 expression. These findings provide the potential for creating a functional, organized lymphatic system through the engineering of vascularized lymphatic tissue via AV loop cultivation, offering an applicable treatment option for lymphatic defects.
Veröffentlicht: August 10, 2025
Gesehen am 15.12.2025